Pengaruh Penerapan Teknik Pointilis Dalam Menggambar Lingkungan Sekitar Terhadap Peningkatan Kreativitas Seni Rupa Siswa Kelas 3 Madrasah Ibtidaiyah Negeri 4 Kota Medan - Khairunnisa Al Izzati; Putra Afriadi; Nurhairani; Apiek Gandamana; Try Wahyu Purnomo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Creativity is one of the key 21st-century competencies that needs to be developed starting in elementary school. Visual arts education in elementary school serves as a strategic means of fostering students’ creativity; however, teaching practices are still dominated by conventional techniques that lack variety, leading to a stagnation of creativity, particularly in terms of originality and elaboration. This study aims to determine the effect of applying simple pointillism techniques in drawing the surrounding environment on the improvement of visual arts creativity among third-grade students at State Elementary School 4 in Medan. This study used a quasi-experimental method with a pretest-posttest control group design. The research sample consisted of 66 students, comprising 33 students in the experimental class and 33 students in the control class. Data were collected through a practical drawing test, which was assessed using a creativity rubric based on the indicators of fluency, flexibility, originality, and elaboration, and then analyzed using an independent samples t-test. The results showed a significance value (Sig. 2-tailed) of 0,001 < 0,05, indicating a significant effect of applying the simple pointillism technique on the improvement of students’ visual arts creativity. The average gain score for the experimental group was 12,60, which was higher than that of the control group 10,30. Improvements were observed in all four aspects of creativity, with the most significant improvements in the aspects of originality and elaboration. In addition, the application of the pointillism technique with the theme of drawing the surrounding environmentmade learning more contextual and meaningful. Thus, the simple pointillism technique is effective for use in visual arts education in elementary school.